PCDDs, PCDFs, and PCBs concentrations in breast milk from two areas in Korea: body burden of mothers and implications for feeding infants - Yang, JY; Shin, DC; Park, S; Chang, YS; Kim, DH; Ikonomou, MG (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
We determined breast milk concentration of polychlorinated dibenzo-p-dioxins (PCDDs)/polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) in 24 mothers living in Korea, and assessed the maternal body burden based on PCDDs/PCDFs and PCBs concentrations in breast milk and an infant intake rate through breast-feeding based on their concentration in breast milk. PCDDs/PCDFs and PCBs levels in breast milk from primipara mothers were found to be higher than those from multipara mothers. For total PCDDs/PCDFs TEQ level, 2,3,4,7,8-PeCDD was the predominant congener, and the proportion of 2,3,7,8-TCDD was less than 3% of total PCDDs/PCDFs TEQ level. For PCBs TEQ level, PCB-126 was the predominant congener. Maternal body burden levels of PCDDs/PCDFs and PCBs based on their concentrations in breast milk were 268-622 TEQ ng. The daily dioxin intakes of mothers were predicted to be 0.78. 2.18 TEQ pg/kg/day for PCDDs/PCDFs and 0.34-0.66 TEQ pg/kg/ day for PCBs. For the first year, the body burden of an infant was predicted to be 212 TEQ ng and the daily intake of an infant was predicted to be 85 TEQ pg/kg/day, assuming the mean dioxin-related compounds concentration (27.54 TEQ pg/g fat). (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: DIBENZO-P-DIOXINS; POLYCHLORINATED-BIPHENYLS PCBS; DICHLORODIPHENYL DICHLOROETHENE DDE; THYROID-HORMONE STATUS; FORMULA-FED INFANTS; ORGANOCHLORINE PESTICIDES; POSTNATAL EXPOSURE; NEUROLOGICAL CONDITION; CHLORINATED DIOXINS; ADIPOSE-TISSUE